The effects of adrenomedullin in traumatic brain injury - DENİZBAŞI ALTINOK, ARZU; ÖZPOLAT, ÇİĞDEM; AKOĞLU, HALDUN (ELSEVIER SCIENCE INC, 2013)
Traumatic brain injury (TBI) is a common cause of death and disability throughout the world. A multifunctional peptide adrenomedullin (AM) has protective effects in the central nervous system. We evaluated AM in an animal model as a therapeutic agent that reduces brain damage after traumatic brain injury. A total of 36 rats was divided into 3 groups as sham, head trauma plus intraperitoneal (ip) saline, and head trauma plus adrenomedullin ip. The diffuse brain injury model of Marmarou et al. was used. Blood samples were taken from all groups at the 1st, 6th and 24th hours for analysis of TNF-alpha (tumor necrosis factor-alpha), IL-1 beta (interleukin-1 beta) and IL-6 (interleukin-6) levels. At the end of the study (at the 24th hour) a neurological examination was performed and half of the rats were decapitated to obtain blood and tissue samples, the other half were perfused transcardiacally for studying the histopathology of the brain tissue. There were no statistically significant changes in plasma levels of IL-1 beta, IL-6 and TNF-alpha relative to the sham group. Also, changes in tissue levels of malonedialdehyde, myeloperoxidase and glutathione were not statistically significant. However, neurological scores and histopathological examinations revealed healing. AM individually exerts neuroprotective effects in animal models of acute brain injury. But the mechanisms of action remain to be assessed. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Adrenomedullin; Traumatic brain injury; Myeloperoxidase; MDA; GSH; IL-6; CEREBRAL-ARTERY OCCLUSION; ISCHEMIC BRAIN; CELL-DEATH; RATS; MODEL